Enhancement load balancing in failover web server by using HTTP-response status techniques with pfsense opensource / Muhammad Hafiz Ramli - Ramli, Muhammad Hafiz (2020)
networking. The primary function of a load balancing is to distribute user requests or network traffic load efficiently across multiple servers or a cluster of servers, which it guarantees high availability and reliability by sending the workload only to servers that are ready and online. The method of election of the resources behind the load balancer will require some algorithms and techniques to process the client request. There are few load balancing algorithms available that help load balance works efficiently across multiple servers. HTTP-response status techniques are used in the load balancing to ensure the web page is accessible across multiple web server. Furthermore, this research will evaluate the number of success rate for the user that successfully load the web page. Besides, notification of the HTTP-response status will be developed for the web server. Next, this paper will discuss the current approach used for web server load balancing to provide high availability system. Then, this paper will propose the architecture design and techniques will use during the implementation stage. Moreover, there will be a simulation with the research parameter. Based on the scenario created, the results and finding will be analysed and discussed. In conclusion, based on the ten (10) scenario, the failure error 404 and 500 occur in ICMP based monitoring, which in the network layer while congestion issue in HTTP based monitoring, which is in the application layer. Increasing the number of failures causes the number of failures of successfulness rate in ICMP based and congestion in HTTP based monitoring. Meanwhile, an email notification was introduced in ICMP and HTTP based monitoring as a notification to the administrator when the failure occurs.